BAHASA BALI USIA ANAK-ANAK : KAJIAN METABAHASA SEMANTIK ALAMI - Arnawa, I Nengah (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 16 (2009): March 2009, 2009)
Abstract This study is based on the Natural Semantic Metalanguage (NSM) theory as proposed by Wierzbicka (1996a) considering the indication that children can master universal semantic features earlier. It results in the universal primitive hypothesis in semantic acquisition by children The mastery of words of Balinese language of 4-6 year old children are predominated by verb (42.07%), followed by noun then (36.55%). However, noun is in higher frequency of use (34.95%) than the verb (30.98%). Among all the words by the children, physical words used are 88.80% and mental words used are 11.20%. The most predominant linguistic idiosyncrasy in the Balinese language of children is overgeneralization. Based on the analysis, it is known that the semantic primes in Balinese is represented by the neutral style or kepara for such vocabulary style is unmarked and generic. There are sixty semantic primes found in Balinese. Out of which the 4-6 year old children are able to produce 58 semantic primes in their utterances. The semantic primes which are not produced by the Balinese children in such a case are AKLINYENGAN ‘A MOMENT’ and MIRIB ‘MAYBE’. The disappearance of semantic primes AKLINYENGAN is due to the uncertainty of the lexical reference and similarly MIRIB ‘MAYBE’ disappears because of the cognitive limitedness of the children so that they are not able to use the knowledge they have in order to predict what is going to happen. The canonic sentence is a distributional pattern of the semantic primes in the linguistic expression of reality. The semantic primes of Balinese having the widest distribution are ICANG ‘I’ and BENA ‘YOU’. The 4-6 year old children are not able to build up a sentence using ICANG ‘I’ and BENA ‘YOU’ as psychological objects.